Family-based association study of the arsenite methyltransferase gene (AS3MT, rs11191454) in Korean children with attention-deficit hyperactivity disorder. (February 2015) - Park, Subin; Park, Jong-Eun; Yoo, Hee Jeong; Kim, Jae-Won; Cho, Soo-Churl; Shin, Min-Sup; Cheong, Jae Hoon; Han, Doug Hyun; Kim, Bung-Nyun
Abstract : We examined the association between the selected polymorphisms in two candidate genes, the arsenite methyltransferase gene ( AS3MT, rs11191454) and the inter-α-trypsin inhibitors heavy chain-3 gene ( ITIH3, rs2535629), and attention-deficit hyperactivity disorder (ADHD) in a Korean population. A total of 238 patients with ADHD, along with both of their biological parents, were recruited. The children were administered intelligence quotient tests, whereas their parents completed the Child Behavior Checklist. In the transmission disequilibrium test on 181 trios, we found overtransmission of the A allele at the AS3MT rs11191454 polymorphism in children with ADHD ( χ 2 =8.81, P =0.003). However, there was no preferential transmission at the ITIH3 rs52535629 polymorphism ( χ 2 =0.14, P =0.707). Our results provide preliminary evidence for the overtransmission of the A allele at the AS3MT rs11191454 polymorphism in ADHD.